Developmental Stages of Bell Pepper Influence the Response to Far-Red Light Supplements in a Controlled Environment - Awa Marina Mouliom-Ntapnze; Georges Yannick Fangue-Yapseu; Tagnon D. Missihoun (Agronomy)
Far-red (FR) additions to white or red/blue light resulted in improved dry biomass and fruit nutritional quality. Despite these positive effects, FR supplementation was also found to induce the abortion of flowers and fruits. We hypothesized that the timing and duration of the FR supplements determine the positive or negative effects of the FR supplement on the plant. To examine this hypothesis, we compared the effect of a gradient of FR supplements (5.5, 12, and 18.1 μmol m−2 s−1) on bell pepper plants (Capsicum annuum cv. Margrethe) when they were exposed to the FR supplements at the beginning of their vegetative growth phase to when FR supplementation only began at the generative phase. We found that 12 and 18.1 μmol m−2 s−1 of FR supplements resulted in a higher yield than 5.5 μmol m−2 s−1 of FR supplements, but FR supplementation from the onset of flowering delayed fruit ripening by 5–8 days and decreased fruit yield compared to FR supplementation that began at seedling transplantation. These results indicate that the positive effect of the FR supplements on the pepper plants of the cultivar Margrethe depends on the plant’s stages of development, and a much lower FR intensity may suffice to enhance growth and yield.